2022
DOI: 10.1038/s41420-022-00969-8
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α-regulated lncRNA-TUG1 promotes mitochondrial dysfunction and pyroptosis by directly binding to FUS in myocardial infarction

Abstract: Myocardial infarction (MI) is a fatal heart disease that affects millions of lives worldwide each year. This study investigated the roles of HIF-1α/lncRNA-TUG1 in mitochondrial dysfunction and pyroptosis in MI. CCK-8, DHE, lactate dehydrogenase (LDH) assays, and JC-1 staining were performed to measure proliferation, reactive oxygen species (ROS), LDH leakage, and mitochondrial damage in hypoxia/reoxygenation (H/R)-treated cardiomyocytes. Enzyme-linked immunoassay (ELISA) and flow cytometry were used to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 40 publications
0
14
0
2
Order By: Relevance
“…4i&4j). It was reported that cells in hypoxia would lead to mitochondrial damage 42 , and with a compact core in the CSps, the ULA group showed lower oxidative stress resistance. In contrast, under the proper stimulation induced by OPC, the CSps in the OPC group could acquire the ability to resist oxidative stress before transplantation (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…4i&4j). It was reported that cells in hypoxia would lead to mitochondrial damage 42 , and with a compact core in the CSps, the ULA group showed lower oxidative stress resistance. In contrast, under the proper stimulation induced by OPC, the CSps in the OPC group could acquire the ability to resist oxidative stress before transplantation (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Experiments have confirmed that cardiomyocyte apoptosis plays an important role in acute heart failure, and the increase of HIF-lα expression is conducive to the survival of cardiomyocytes. [37] Inflammation plays an important role in the occurrence and development of HFpEF. AGE is a kind of advanced glycation end product formed by non-enzymatic catalysis, and RAGE is its specific receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis was evaluated with FAM-FLICA Caspase-1 Assay Kits (ImmunoChemistry, USA) in accordance with the manufacturer's protocol. 17 Samples were mixed with FLICA and propidium iodide (PI) and then incubated in the dark at 37 C for 1 h. Flow cytometry was then applied to analyze pyroptosis (BD Biosciences, San Jose, USA). Double-positive cells were considered pyroptotic cells.…”
Section: Detection Of Pyroptosis By Flow Cytometrymentioning
confidence: 99%